An overview of the appendicular skeletal anatomy of South American titanosaurian sauropods, with definition of a newly recognized clade - Gonzalez Riga, Bernardo Javier (2019)
In the last two decades, the number of phylogenetically informative anatomical characters recognized in the appendicular skeleton of titanosaurian sauropod dinosaurs has increased dramatically with the discovery of new and comparatively complete specimens. here we provide an overview of the appendicular skeletal morphology of South American titanosaurs and discuss its significance for phylogenetic reconstruction. the appendicular skeletal diversity of South American titanosaurs is substantially greater than was initially appreciated. Moreover, some regions of the appendicular skeleton, such as the pes, exhibit remarkable variability in form. Multiple synapomorphies of titanosauria and the less inclusive clades Lithostrotia and Saltasauridae consist of characters of the girdles and limbs. Although the phylogenetic definitions of titanosaurian clades such as Saltasaurinae and Lognkosauria are stable, the taxonomic content of these clades has varied in recent analyses depending on the phylogenetic topology recovered. Within titanosauria, the results of four recent, largely independent analyses support the existence of a derived titanosaurian lineage distinct from the ‘Saltasaurinae line,’ which is herein termed Colossosauria. At present, this clade is mainly comprised by taxa within Lognkosauria and rinconsauria, and is useful in discussions of titanosaurian lower-level relationships.